FOOD SELF-SUFFICIENCY OF UKRAINE AS COMPARED TO THE EUROPEAN UNION - Iwona Szczepaniak; Piotr Szajner (Annals of the Polish Association of Agricultural and Agribusiness Economists)
Food self-sufficiency is one of the factors determining the food security of individual countries. The purpose of the research was to assess food self-sufficiency in basic plant and animal products of Ukraine in comparison with the European Union. To assess food self-sufficiency, the SSRi index was used, i.e. the ratio of the volume of production of the most important products of plant and animal origin to the volume of their domestic consumption. USDA, FAOSTAT and CSO data were used in the study. The study covered the years 2019-2023. A comparative analysis of the self-sufficiency in basic plant and animal products of the Ukrainian and EU agri-food sectors showed significant differences. Ukraine has high self-sufficiency in cereals and oilseeds, while the EU has only small surpluses of cereals and is a net importer of oilseeds. The self-sufficiency of Ukraine’s sugar and vegetable industries is comparable to that of the EU. On the fruit market, by contrast, Ukraine and the EU are not self-sufficient. Ukraine’s self-sufficiency on the animal products market is much lower than on the vegetable products market. Ukraine is primarily self-sufficient in poultry, but not in pork and dairy products. The EU is self-sufficient in most animal products. Taking into account the production potential and food self-sufficiency of Ukraine, it should be expected that the future accession of Ukraine to the EU will strengthen the position of the EU in the world market of agricultural raw materials and improve its food security and resilience to crisis phenomena. However, it may pose a threat to many sectors of the EU agri-food sector and force adjustment processes on them.